1998
DOI: 10.1021/jp980745f
|View full text |Cite
|
Sign up to set email alerts
|

Localized Electronic Excitations in Phenylacetylene Dendrimers

Abstract: Electron-hole pairs created upon optical excitation of conjugated dendrimers (fractal antenna macromolecules) are shown to be localized within segments connected by benzene rings substituted at the meta-position. The absorption spectra of two families of dendrimers are analyzed using collective electronic normal modes representing the changes in charge and bond-order distributions induced by the optical field. The present approach may be used in the design of artificial light-harvesting antennae with controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
230
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 209 publications
(240 citation statements)
references
References 27 publications
4
230
0
Order By: Relevance
“…The groundstate and 10 excited-state electronic energies, gradients, and nonadiabatic coupling vectors were calculated at the configuration interaction singles (CIS) level using the collective electronic oscillator (CEO) code 22 combined with the Austin model 1 (AM1) Hamiltonian. 46 These methodologies have been previouslysuccessfullyappliedtodescribeconjugatedpolymers, 21,47 carbon nanotubes 48 and other organic molecular materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The groundstate and 10 excited-state electronic energies, gradients, and nonadiabatic coupling vectors were calculated at the configuration interaction singles (CIS) level using the collective electronic oscillator (CEO) code 22 combined with the Austin model 1 (AM1) Hamiltonian. 46 These methodologies have been previouslysuccessfullyappliedtodescribeconjugatedpolymers, 21,47 carbon nanotubes 48 and other organic molecular materials.…”
Section: Methodsmentioning
confidence: 99%
“…23, 47 The CEO model uses realspace wave packets representing the single-electron density matrix. The optical properties of the system are related directly to the motions of charges and electronic coherences.…”
Section: Introductionmentioning
confidence: 99%
“…CEO calculations have previously been carried out on organic molecules and oligomers. 13,16,17 It was recently shown that the calculation of the electronic properties of dendrimers can be simplified by constructing a Frenkel exciton Hamiltonian from the monomer, dimer, and trimer units constituting the dendrimer. 16,18 In this paper we present for the first time calculations on entire dendrimer structures, which allow a real space visualisation of the distribution of excitations in The dendrimers studied are shown in Fig.…”
mentioning
confidence: 99%
“…A consequence of this is that excitations generated on the dendrons will rapidly relax to the lower energy core mode due to the built-in energy gradient. 17,18 Note that the third benzene ring of the DSB unit (C 17 -C 22 ) is conjugated with both the dendrons and the core so that it can contribute both to core excitations and also to dendron excitations.…”
mentioning
confidence: 99%
“…The efficiency of photosynthetic units -especially the photobacterial systems and the excitation energy relocates across the structure [31][32][33], ultimately being funneled into the core [34]. Striking examples of this principle can be seen in classic work on perylene-functionalised phenylacetylene dendrimers [35,36].…”
Section: Dendrimersmentioning
confidence: 99%